Lexical Density of Reading Materials in An English Textbook: A Content Analysis - Maufiroh, Yuni Lailatul; Hussen, Bannaga Taha Elzubair; Femilia, Praptika Septi (Journal of Language Intelligence and Culture, 2024)
In reading, students are required to learn to comprehend the content of the text. Lexical density is one of the factors that influences students’ reading comprehension. Lexical density is a condition of words’ proportion in a text, which shows the ratio of content words (CW) and grammatical function words (GFW). This research used the “Passport to the World” English textbook for the 8th grade of junior high school to be analyzed. This study aims to find out the genres of reading materials offered by the curriculum 2013 found in the textbook and to examine the lexical density of the reading materials in the textbook. A qualitative approach was applied, while content analysis was used as the research design. Data were collected with document analysis. The findings showed that there are 3 genres of reading materials, among 5 genres offered by the curriculum 2013, included in the textbook such as descriptive, recount, and functional texts in the form of announcements. From those, it was found that two texts were categorized as low lexical density, 11 texts were categorized as medium lexical density, and four texts were labeled as high lexical density. In addition, the composition of this text did not reach the ideal ratio of 1:2:1 for index difficulty. However, this textbook can still be suggested to be used in the class with some usage modifications in the classroom.